ICRF - volume charge - antenna edge interactions in the torsatrons U-3M and U-2M Part 1. Formation of a volume space charge (VSC) of positive ions - Berezhnyj, V.L. (Вопросы атомной науки и техники, 2016)
A feature of fusion plasma rf discharges is the formation of near-wall volume-space charges (VSC) of positive
ions. Nonlinear properties of VSC layers exert a determining influence on the rf discharge characteristics. The rf
discharge includes the inductive and capacitive elements of the power input into the plasma, i.e. it is a hybrid discharge. Особенностью ВЧ-разрядов термоядерной плазмы является образование пристеночных объёмных пространственных зарядов (ОПЗ) положительных ионов. Нелинейные свойства слоёв ОПЗ оказывают определяющее влияние на характеристики ВЧ-разрядов. ВЧ-разряд включает индуктивную и ёмкостную компоненты ввода мощности в плазму, т.е. является гибридным разрядом. Особливістю ВЧ-розрядів термоядерної плазми є створення пристіночних об’ємних просторових зарядів
(ОПЗ) позитивних іонів. Нелінійні властивості шарів ОПЗ чинять значущий вплив на характеристики ВЧ-
розрядів. ВЧ-розряд включає індуктивну та ємнісну компоненти введення потужності в плазму, тобто є гібридним розрядом.